Age-related macular degeneration (AMD) mitochondria modulate epigenetic mechanisms in retinal pigment epithelial cells. (December 2019) - Nashine, Sonali; Nesburn, Anthony B.; Kuppermann, Baruch D.; Kenney, M. Cristina
Abstract: Mitochondrial damage and epigenetic modifications have been implicated in the pathogenesis of Age-related Macular Degeneration (AMD). This study was designed to investigate the effects of AMD/normal mitochondria on epigenetic regulation in human transmitochondrial retinal pigment epithelial (RPE) cells in vitro . Human RPE cybrid cell lines were created by fusing mitochondria-deficient (Rho0) ARPE-19 cells with platelets obtained from either AMD patients (AMD cybrids) or normal subjects (normal cybrids). Therefore, all cybrids had identical nuclei (derived from ARPE-19 cells) but mitochondria derived from either AMD patients or age-matched normal subjects. AMD cybrids demonstrated increased RNA/protein levels for five methylation-related and four acetylation-related genes, along with lower levels of two methylation and three acetylation genes compared to normal cybrids. Demethylation using 5-Aza-2′-deoxycytidine (DAC) led to decreased expression of VEGF-A gene in AMD cells. Trichostatin A (TSA), an HDAC inhibitor, also influenced protein levels of VEGF-A, HIF1α, NFκB, and CFH in AMD cells. Our findings suggest that retrograde signaling leads to mitochondria-nucleus interactions that influence the epigenetic status of the RPE cells and this may help in the identification of future potential therapeutic targets for AMD. Highlights: AMD mitochondria regulate epigenetic mechanisms i.e., methylation and acetylation. Demethylation using DAC affects VEGF-A gene expression in AMD cells. DAC and TSA could be potential targets for therapeutic intervention in AMD.